2014
DOI: 10.1038/aps.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane post-conditioning protects isolated rat hearts against ischemia-reperfusion injury via activation of the ERK1/2 pathway

Abstract: Aim: To investigate the role of extracellular signal-regulated kinases (ERKs) in sevoflurane post-conditioning induced cardioprotection in vitro. Methods: Isolated rat hearts were subjected to 30 min ischemia followed by 120 min reperfusion (I/R). Sevoflurane post-conditioning was carried out by administration of O 2 -enriched gas mixture with 3% sevoflurane (SEVO) for 15 min from the onset of reperfusion. Cardiac functions, myocardial infarct size, myocardial ATP and NAD + contents, mitochondrial ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Interestingly, sevoflurane exposure alone increased phosphorylation of Erk1/2 slightly, but PD98059 treatment alone could significantly attenuate the increase of phosphorylation of Erk1/2 induced by OGD/R. It has been found that, sevoflurane post-conditioning inhibits myocardial cell death via activation of Erk1/2 pathway [11,25]. Our study indicated that, sevoflurane post-conditioning could protect primary rat cortical neurons against OGD/R mediated by activation of Erk1/2.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, sevoflurane exposure alone increased phosphorylation of Erk1/2 slightly, but PD98059 treatment alone could significantly attenuate the increase of phosphorylation of Erk1/2 induced by OGD/R. It has been found that, sevoflurane post-conditioning inhibits myocardial cell death via activation of Erk1/2 pathway [11,25]. Our study indicated that, sevoflurane post-conditioning could protect primary rat cortical neurons against OGD/R mediated by activation of Erk1/2.…”
Section: Discussionmentioning
confidence: 60%
“…Excessive apoptosis is associated with myocardial ischemia, I/R injury as well as postischemia cardiac remodeling [18], while infarct size is an independent indicator effective in predicting mortality after infarction [19]. In the current work, we observed that Sev worked as a cardio-protector against injury induced by myocardial I/R by reducing LVEF, LVFS, myocardial infarct size and apoptosis rate, indicating the bene cial role of Sev on I/R injury [20,21]. Moreover, Sev was found to diminish NEAT1, which was enhanced in mice with myocardial I/R, by microarray analysis.…”
Section: Discussionsupporting
confidence: 52%
“…Sevoflurane, a commonly used inhalation anaesthetic agent in clinical practice, is considered the cornerstone of this drug class because of its favourable characteristics, including smooth induction of anaesthesia, rapid post-operative recovery and minimal impact on hemodynamics. Several studies have demonstrated that SpostC can protect healthy myocardium from I/R injury, [6][7][8][9]28 but the underlying mechanism remains unclear. Interestingly, our previous studies found that the protective effects of SpostC on isolated myocardial mitochondria can be attributed to the upregulation of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%